Extraction, structural characterization, and antioxidant activity of polysaccharides derived from Arctium lappa L. - Gao, Dandan; Chen, Hong; Li, Haixing; Yang, Xuhua; Guo, Xingchen; Zhang, Yuxuan; Ma, Jinpu; Yang, Jutian; Ma, Shuwen (Frontiers in Nutrition, 2023)
Arctium lappa L. root has high nutritional and medicinal value, and has been identified as one of the health food raw materials by the china’s Ministry of Health. In present study, an aqueous two-phase system (ATPS) of polyethylene glycol (PEG)-(NH4)2SO4 was used to extracted Arctium lappa L. polysaccharides (ALPs) from Arctium lappa L. root, the optimal extraction conditions of crude ALPs were optimized by using single-factor experiment and response surface methodology. The optimized extraction parameters for extraction ALPs were as follows: PEG relative molecular weight 6000, quality fraction of PEG 25%, quality fraction of (NH4)2SO4 18%, extraction temperature 80°C. Under these conditions, the extraction rate of ALPs could reach at 28.83%. The structure and composition of ALPs were determined by fourier infrared spectrum (FI-RT), scanning electron microscopy (SEM), and HPLC. The results showed that ALPs were typical acidic heteropolysaccharides, having uneven particle size distribution, irregular shape and a rough surface. ALPs were mainly composed of glucose, rhamnose, arabinose, and galactose with a molar ratio of 70.19: 10.95: 11.16: 6.90. In addition, ALPs had intense antioxidant activity in vitro with IC50 values in ·OH radical (1.732 mg/mL), DPPH radical (0.29 mg/mL), superoxide anion (0.15 mg/mL) scavenging ability.